The Arabidopsis Cytosolic Ribosomal Proteome: From form to Function - Carroll, Adam J. (Frontiers in Plant Science, 2013)
The cytosolic ribosomal proteome of Arabidopsis thaliana has been studied intensively by a range of proteomics approaches and is now one of the most well characterized eukaryotic ribosomal proteomes. Plant cytosolic ribosomes are distinguished from other eukaryotic ribosomes by unique proteins, unique post-translational modifications and an abundance of ribosomal proteins for which multiple divergent paralogs are expressed and incorporated. Study of the A. thaliana ribosome has now progressed well beyond a simple cataloging of protein parts and is focused strongly on elucidating the functions of specific ribosomal proteins, their paralogous isoforms and covalent modifications. This review summarises current knowledge concerning the Arabidopsis cytosolic ribosomal proteome and highlights potentially fruitful areas of future research in this fast moving and important area.